2015
DOI: 10.1371/journal.pone.0140052
|View full text |Cite
|
Sign up to set email alerts
|

Increased Soluble Urokinase-Type Plasminogen Activator Receptor (suPAR) Levels in Plasma of Suicide Attempters

Abstract: The soluble form of the urokinase receptor, suPAR, has been suggested as a novel biomarker of low-grade inflammation. Activation of the immune system has been proposed to contribute to the development of depression and suicidal behavior. In order to identify depressed and suicidal individuals who could benefit from an anti-inflammatory treatment, a reliable biomarker of low-grade inflammation is vital. This study evaluates plasma suPAR levels as a biomarker of low-grade inflammation in patients with major depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…The elevated P-suPAR level, but not P-high-sensitivity CRP levels, in patients with MDD is in accordance with our previous study18 that also showed significantly higher P-suPAR levels in depressed patients but no significant difference in P-high-sensitivity CRP levels between depressed patients and healthy controls. The biomarkers suPAR and CRP may reflect different aspects of low-grade inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…The elevated P-suPAR level, but not P-high-sensitivity CRP levels, in patients with MDD is in accordance with our previous study18 that also showed significantly higher P-suPAR levels in depressed patients but no significant difference in P-high-sensitivity CRP levels between depressed patients and healthy controls. The biomarkers suPAR and CRP may reflect different aspects of low-grade inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…Serum suPAR levels are found to be lower in patients with BD with acute periods than in patients with euthymic episodes and healthy controls (29). In addition, it was found that individuals with high suPAR levels were more likely to attempt to commit suicide (13).…”
Section: Discussionmentioning
confidence: 97%
“…suPAR molecule is involved in various immuno-logical functions, such as cell adhesion, migration, differentiation, proliferation, and angiogenesis (10). suPAR, a proinflammatory molecule, and its relationship with psychiatric illnesses have been the subject of many studies, and the role of suPAR in psychiatric diseases has not yet been fully elucidated (11)(12)(13). suPAR levels in patients with schizophrenia and depression and who attempted suicide were found to be higher than those in the healthy control groups (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Also, a recent study indicated that a decrease in Interleukin-6, a pro-inflammatory cytokine, was associated with a decrease in depressive symptoms in first episode schizophrenia patients [ 46 ]. Moreover, results from non-schizophrenia samples show an association between suPAR levels and depression [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Large population-based studies have revealed a positive association between blood levels of suPAR and the following factors; female sex, increasing age, unhealthy lifestyle, cardiovascular risk factors, diabetes, as well as low socioeconomic status [ 18 20 ]. Additionally suPAR levels are elevated in patients with MDD [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%